Government Strategy in Handling Stunting in Telaga Biru District, Gorontalo Regency - Pakaya, Riskawaty; Mohi, Widya Kurniati; Idji, Rusly Abdurrahman; Luawo, Salma Rivani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aimed to investigate the government strategies in addressing stunting in Telaga Biru District, Gorontalo Regency. The study employed a qualitative approach with a descriptive research design. A strategy is an action chosen to achieve organizational goals; in this case, the strategy within the scope of govemment refers to the actions or decisions made to address a specific issue. The strategies implemented by the Telaga Biru District Government in addressing stunting included programs focused on improving the nutritional intake of stunted children. These programs included the Foster Parent Program (Genting), Posyandu (integrated health posts), sanitation improvements, and the provision of clean water. The results indicated that the strategies of the Telaga Biru District Government in preventing stunting were effective, as they had shown a decrease in stunting rates.